Literature Review of Renewable Energy in the Tourism Industry - ÁSVÁNYI, Katalin; JUHÁSZ-DÓRA, Katalin; JÁSZBERÉNYI, Melinda; MICHALKÓ, Gábor (Journal of Environmental Management and Tourism, 2017)
The increasing importance of renewable energy in the service sector - and specifically in the tourism industry - has developed into a new research topic. Renewable energy, of course, plays a significant role in tourism, in many respects, and especially in relation to such matters as energy efficiency, sustainability and cost reduction. To date, however, no systematically collated review of the literature dealing with the topic has appeared, and so this study attempts to fill this gap in the literature by means of a content analysis of the research publications focusing on the use of renewable energy in the tourism industry. Through a comprehensive review of the literature, our study identifies what is known about renewable energy in the service sector in general and in the tourism industry in particular, although it is clear from this that research into renewable energy in tourism is still at an early stage. The aim of our study, therefore, is a better insight into the role of renewable energy in tourism, mainly by examining accommodation and focusing on destinations. We hope that the system-based approach of our study will open more doors to renewable energy. This, in turn, should support the basic principle of sustainability.